2016
DOI: 10.1177/1049731514568024
|View full text |Cite
|
Sign up to set email alerts
|

Head Start Impact on Social–Emotional Outcomes for Children With Disabilities

Abstract: Objective: Using the Head Start Impact Study data, this study examines Head Start's impacts on social-emotional outcomes for children with disabilities. Method: Among 4,442 children, 570 children were reported to have disabilities. Ordinary least squares regression was used to determine whether the number of disabilities, having an individualized education plan (IEP), and receiving Supplemental Security Income (SSI) affect social-emotional outcomes for children with disabilities and whether Head Start's impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 32 publications
0
8
1
Order By: Relevance
“…This finding contradicts a previous study (Lee, Calkin, & Shin, 2015) that found children who had multiple disabilities generally had negative social-emotional outcomes. Among children who had multiple disabilities in the present study, speech impairment was the comorbid disability diagnosed in most cases.…”
Section: The Associations Of Number Of Disabilities and Iep With Cogncontrasting
confidence: 83%
See 1 more Smart Citation
“…This finding contradicts a previous study (Lee, Calkin, & Shin, 2015) that found children who had multiple disabilities generally had negative social-emotional outcomes. Among children who had multiple disabilities in the present study, speech impairment was the comorbid disability diagnosed in most cases.…”
Section: The Associations Of Number Of Disabilities and Iep With Cogncontrasting
confidence: 83%
“…The current study expands this examination of differences between Head Start and control group children with disabilities by including measures of language and early academic functioning and by accounting for two other factors that may shape cognitive outcomes for children: IEP receipt and multiple disability status. Further, this study adds to a previous study that examined Head Start's effect on social-emotional outcomes for children with disabilities (Lee, Calkin, & Shin, 2015). This study was determined to be nonhuman subject research since the data do not contain any identifiable personal information as defined by the Department of Health and Human Services [45.…”
Section: Target Samplementioning
confidence: 98%
“…Disabled children tend to have more health-related needs, along with social and environmental factors that prevent them from participating fully in society (Halfon et al, 2012). Children with disabilities experience higher rates of social-emotional issues, which have long-term implications for an increase in the risk of further disabilities being diagnosed, as well as links to poverty and Supplemental Security Income dependency (Lee et al, 2016). In addition, children with disabilities often show deficits in transition and career success and require interventions to increase self-determination (Moore & McNaught, 2014; Zheng et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Zhai et al (2011) found that Head Start had significant and consistent effects on improvement in children’s cognitive development at age 5 years, but the study did not distinguish between students with and without disabilities. Although Lee et al (2016) discussed the outcomes for children with disabilities at age 5 years, this study did not investigate the outcomes at later ages. While evidence indicates short-term benefits to Head Start participation, there is little research investigating the long-term outcomes of Head Start participation solely on children with disabilities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation